Police Professional Ethics in Law Enforcement in Indonesia - Chaniago, Dinda ayu Arini; Lubis, Fauziah; Siregar, Fitria Mukhtar (Kadiri Islamic University, 2025)
This study investigates the significance of professional ethics in fostering professionalism, integrity, and credibility within the Indonesian National Police as a law enforcement institution. The research highlights the persistent issues of ethical misconduct and abuse of power, which have contributed to the decline of public trust toward the police. The study is grounded in the urgency to strengthen the enforcement of the professional code of ethics as a means to develop an integrity-based, human-oriented police institution that gains public confidence. Using a normative legal approach, this research analyzes various legal frameworks, academic literature, and secondary data related to the implementation of professional ethics within the police force. The findings indicate that professional ethics play a vital role in aligning police conduct with the values ​​of justice, accountability, and humanity. Both internal factors, such as leadership and organizational culture, and external influences, including public oversight and media involvement, significantly affect the effectiveness of ethical enforcement. Furthermore, consistent moral development, ethical education, and fair disciplinary measures have been shown to enhance public trust in the police. In ethics conclusion, reinforcing professionals is essential for establishing a competent and integrity driven police institution. Sustained leadership commitment, proportional sanctions, and transparency to public scrutiny are key to ensuring accountability and fairness in Indonesia's law.